Effect of Day Length and Feed/Water Regime on Induction of Feather Moult and Subsequent Laying Performance in the Domestic Fowl - Oguike, M.A.; Igboeli, G.; Ibe, S.N.; Uzoukwu, M. (International Journal of Poultry Science, 2004)
Investigations were carried out to ascertain the effectiveness of some conventional restriction techniques on feather moult. The techniques used to induce moult, which were imposed for 10 days, were: natural day length with feed and water ad libitum, natural day length with water but no feed, natural day length with no feed and no water, reduced day length with feed and water ad libitum, reduced day length with water but no feed, reduced day length with no feed and no water designated as T1, T2, T3, T4, T5 and T6, respectively, with T1 as the control. A total of 60 old layers aged 85 weeks were randomly assigned to each treatment in a completely randomized design, with three replicates. After the 10 days of moult induction, all the moulting hens were returned to the same conditions as the control. The results of the study revealed that shedding of feathers began 10 days from the beginning of moult induction with the feathers of the moulting birds appearing ruffled. There were no regular patterns in the shedding of wing and body feathers. Also the shedding of the two wings occurred simultaneously. The duration of shedding of wing feathers by birds in T4 was significantly (P<0.05) longer than for the other groups, probably because of the severity of restriction of light, feed and water for T2, T3, T5 and T6. Shedding of primary and secondary wing feathers ranged from 7 to 51 days. The T4 showed significantly (P<0.05) lower % egg production than T2, T3, T5, T6, after feather moulting. Also the T4 attained peak production later than the other groups following induction of feather moult.